Breastfeeding during the COVID-19 pandemic - Chanda, Bwalya Mpelwa; Chen, Xiao-Qing (Frontiers in Pediatrics, 2023)
Because of the COVID-19 pandemic, mother to child transmission of the SARS CoV-2 virus has become an important issue threatening the health of neonates and infants. It is critical that infants are breastfed as breast milk is the most suited type of feed for the infant. It is also an important determinant of the health status for both the infant and the mother. However, many concerns have arisen regarding breastfeeding during the time of the pandemic; among them the safety of breastfeeding and the possibility of attendant risk of vertical transmission of the virus. This has become a challenging topic, and is being actively explored. Theoretically, vertical transmission of the virus can occur in the antenatal, intra partum or post natal periods. And considering specifically the postpartum period, breastfeeding has been suspected to be a risk for mother to child transmission of the virus through breast milk. Other than the foregoing, there has been lack of clarity as to whether breastfeeding in special circumstances such as the Neonatal Intensive Care Unit (NICU) and the Nursery should continue; if so, what precautions are supposed to be observed? The important role that milk banks have continued to play over the years has recently become more pronounced; providing pasteurised human donor breast milk to infants. They are a source of safe breast milk in certain situations when the mother’s own breast milk is not available such as maternal illness. The progression of the disease in infected neonates is also under study, and new information is becoming available by the day. Recent developments have led to several types of vaccines against the SARS CoV-2 virus but the question of safety of the vaccine in pregnant and lactating women has come to the fore. Among the areas of particular interest have been whether there is the presence of vaccine materials and vaccine-induced immunoglobulins in breast milk and the possibility of their being transferred to the breastfeeding infant through breast milk. In this background has arisen the question of safety of vaccinating women in this group. Therefore, should breastfeeding continue during the pandemic continue?